A functional lncRNA HOTAIR genetic variant contributes to gastric cancer susceptibility. Issue 1 (3rd January 2015) - Pan, Wenting; Liu, Lisheng; Wei, Jinyu; Ge, Yunxia; Zhang, Jingfeng; Chen, Hongwei; Zhou, Liqing; Yuan, Qipeng; Zhou, Changchun; Yang, Ming
Abstract : Long noncoding RNA (lncRNA) HOX transcript antisense RNA (HOTAIR) acts as an oncogene in gastric cancer development. HOTAIR could induce genome‐wide retargeting of polycomb‐repressive complex 2, trimethylates histone H3 lysine‐27 (H3K27me3) and deregulation of multiple downstream genes. Additionally, as the ceRNA of miR‐331–3p, HOTAIR may modulate HER2 deregulation in gastric cancer cells. We hypothesized that the functional single nucleotide polymorphisms (SNP) in HOTAIR may affect HOTAIR expression and/or its function and, thus, gastric cancer risk. We examined the association between three haplotype‐tagging SNPs (htSNP) across the whole HOTAIR locus and gastric cancer risk as well as the functional relevance of a gastric cancer susceptibility SNP rs920778. Genotypes were determined in two independent hospital‐based case‐control sets that consisted of 800 gastric cancer patients and 1600 controls. The allele‐specific regulation on HOTAIR expression by the rs920778 SNP was examined in vitro and in vivo. We found that the HOTAIR rs920778 TT carriers had a 1.66‐ and 1.87‐fold increased gastric cancer risk in Jinan and Huaian populations compared with the CC carriers ( P = 4.2 × 10 −4 and 6.5 × 10 −5 ). During inspecting functional relevance of the rs920778 SNP, we observed an allelic regulation of rs920778 on HOTAIR expression in both gastric cancer cell lines and tissue samples, with higher HOTAIR expression among T allele carriers. These findings elucidate that functional genetic variants influencing lncRNA expression may explain a portion of gastric cancer genetic basis. © 2015 Wiley Periodicals, Inc.